Analysis of the aerodynamic pressure effect on the fatigue strength of the carbody of high-speed trains passing by each other in a tunnel. (September 2019) - Lu, Yaohui; Zhang, Dewen; Zheng, Heyan; Lu, Chuan; Chen, Tianli; Zeng, Jing; Wu, Pingbo
When two high-speed trains pass through a tunnel, the aerodynamic changes are more complex and drastic than in open air owing to the interference of the tunnel wall and the entry effect. The impact on the carbody fatigue strength is very significant in the fatigue reliability design of the carbody. In this paper, the sequential coupling method was used for the first time to study the effect of pressure waves on the fatigue strength in a large-scale and complex carbody structure. The computational fluid dynamics method was used to calculate and analyze the aerodynamic pressure wave of the intersection of the trains in a long and short tunnel. A full-scale finite element shell model of the carbody structure was established. Then, the time integration method was used to convert the transient pressure wave into the aerodynamic loads bearing by the side wall of the carbody. The inhomogeneous stress concentrations at the restraint points were eliminated by the inertial release method; moreover, a finite element analysis of the carbody was carried out under the combined aerodynamic and mechanical loads. The Goodman fatigue strength curve of the aluminum alloy carbody was drawn. The influence of the aerodynamic load on the fatigue strength of the vehicle body was analyzed and compared under the entry effect of the short tunnel. The results show that the aerodynamic load of the short tunnel has a significant impact on the fatigue strength of the carbody owing to the train's entry effect. The safety factor of the fatigue strength is 15% less than that of the long tunnel aerodynamic load. In this paper, computational fluid dynamics and finite element method were used to analyze and evaluate the impact of the pressure wave on the fatigue strength of the carbody, which is of great reference value in the structural design of the carbody subjected to complex aerodynamic loads.